In vitro interaction of viral haemorrhagic septicaemia virus and leukocytes from trout (Oncorhynchus mykiss) and turbot (Scophthalmus maximus) - Tafalla, Carolina; Figueras Huerta, Antonio; Novoa, Beatriz (Veterinary Immunology and Immunopathology, 1998)
8 páginas, 2 figuras Viral haemorrhagic septicaemia virus VHSV., a well known salmonids pathogen, has also been reported to be pathogenic for turbot Scophthalmus maximus. In the present work, the replication of VHSV was studied in vitro in turbot head kidney macrophages and blood leukocytes. VHSV was able to infect both primary cultures and viral titer increased with time, either inside the cells or in the supernatant. However, no cytopathic effect was observed during the experiments and the titers were always lower than those obtained in the fish cell lines. The number of trout and turbot macrophages after several days of in vitro infection with VHSV was compared with uninfected controls by viable cell count but no significant differences were observed. The number of cells supporting viral replication evaluated by immunofluorescence in trout and turbot was low 8 and 1.7%, respectively. Respiratory burst activity of head kidney macrophages was assayed at different days post-infection, but no significant differences were found between the control and the infected cultures neither in trout nor turbot This research was supported by grant MAR 96-1775 from the Comision Interministerial de Ciencia y Tecnologıa CICYT. Peer reviewed